Influence of orientation on mechanical properties in fused deposition modelling - Kutnjak-Mravlinčić, Suzana (Array, 2020)
In the footwear industry, increasing attention is paid to design-shaped heels. But that design involves production of the complicated geometry, personalised heels (i.g. small series), light weight heels and if possible cheap production. Technology that enables and combines that is additive manufacturing (AM). One of AM low budget technology and machine is fused deposition modeling (FDM). In FDM, product is built layer by layer and with different types and density of inside mesh structures which enables complex geometry and low mass. When walking, the heel is loaded from above with compression force of the person's weight, while lateral, heel is loaded with flexural force and impact. Considering the design of the heel itself, it is necessary to orientate the product correctly in the working space of the machine. Orientation further raises the question of mechanical properties on such produced heel. In this paper it is tested flexural properties of two different orientation considering production of the actual heel. Furthermore, the analysis of the processing parameters (layer thickness, infill density and temperature) have been done to determine their influence on the flexural properties in these two orientations.